Partial replacement of raw matters by natural zeolite in Clarias gariepinus feed - Llanes, J. E.; Castro, M.; Herrera, Magaly (Cuban Journal of Agricultural Science, 2022)
The partial replacement of 3, 5 and 7 % of each raw matter by Cuban natural zeolite in formulations of small fish feeds and Clarias gariepinus fattening was evaluated. Two bioassays were carried out, according to a completely random design with three repetitions. In the growth stage, a total of 225 small fish of 1.03 ± 0.03 g of initial weight were used, distributed in three treatments (0, 3 and 5 % of zeolite). Similarly, in fattening, a total of 135 animals of 10.12 ± 0.05 g of initial weight were used in three treatments (0, 5 and 7 %). A decrease in the protein supplied/fish was recorded, when the levels of zeolite in the rations increased. However, the indicators of growth, feed efficiency and survival were not disadvantaged up to 5 % in the small fish feed and 7 % in the fattening feed. The economic analysis showed that the use of zeolite decreases the costs of the rations and contributes with amounts of earnings for feeding. It is concluded that the partial replacement of up to 5 % of the raw matters by natural zeolite in the small fish feed and 7 % in the fattening feed does not compromise the productive performance of Clarias gariepinus; in addition to having a positive economic effect. Key words: feeding, catfish, mineral, nutrition, zeolite.